Cognitive evaluation in Parkinson's disease: applying the Movement Disorder Society recommendations in a population with a low level of formal education - Rocha, Natalia Pessoa; Carreira, Eduarda Xavier; Prado, Ana Carolina de Almeida; Tavares, Fabíola; Tavares, Mayra; Cardoso, Francisco; Jaeger, Antônio; Souza, Leonardo Cruz de; Teixeira, Antônio Lucio (Arquivos de Neuro-Psiquiatria, 2023)
Background The diagnosis of cognitive disorders in Parkinson disease (PD) can be very challenging. Aiming at establishing uniform and reliable diagnostic procedures, the International Parkinson's Disease and Movement Disorder Society (MDS) commissioned task forces to delineate diagnostic criteria for mild cognitive impairment (MCI) and dementia in PD.Objectives To investigate the applicability of the MDS recommendations for cognitive evaluation in a Brazilian sample of patients with PD with low levels of formal education.Methods A total of 41 patients with PD were subjected to a comprehensive neuropsychological evaluation based on tests proposed by the MDS, which included the Mini-Mental State Examination, the Mattis Dementia Rating Scale (MDRS), the Trail Making Test (TMT) parts A and B, in addition to language and memory skills assessment. Neuropsychiatric and daily functioning features were also evaluated. Spearman correlation analyses were used to evaluate the association between the scores obtained in the cognitive scales and demographic/clinical variables.Results Although none of the participants had a formal diagnosis of dementia, 50% presented some degree of cognitive impairment when considering the results of the MDRS. Of note, a noticeable number of patients was not able to complete the full neuropsychological assessment. The TMT part B was the most difficult task, being completed by only 22 participants (54%). As expected, the greater the educational level, the better the performance on the cognitive tests. Better motor function was also associated with better scores in cognition.Conclusions Adopting strict inclusion/exclusion criteria and a comprehensive clinical evaluation, we found remarkable limitations for the MDS recommendations when individuals with low educational levels are considered. A revision of the current guidelines is necessary considering differences among populations, especially related to formal education.
Keywords: Parkinson Disease; Cognitive Dysfunction; Dementia; Neuropsychological Tests; Educational Status